Expression of tumor necrosis factor Alpha, interleukin-1 and matrix metalloproteinase-9 and pathomorphological changes in acquired middle ear cholesteatoma - Predrag Špirić; Mirjana Gnjatić; Dalibor Vranješ (Биомедицинска истраживања, 2021)
Introduction: The inflammatory mediators play a central role in the pathogenesis of the inflammatory process of the middle ear and cholesteatoma from the aspect of initiating and maintaining the inflammatory response to infection and lesion. The aim of the study was to examine if the presence of acquired cholesteatoma could predict pathomorphological changes of the tympanic cavity mucosa in relation to the control tissue of the inflamed middle ear mucosa and to examine and compare the expression levels of tumor necrosis factor-alpha (TNF-a), interleukin-1 (IL-1) and matrix metalloproteinase 9 (MMP-9) with pathomorphological changes in the middle ear mucosa in chronic otitis media (COM), with and without acquired cholesteatoma (AC). Methods: The immunohistochemical study included 178 patients of both sexes, aged 5 to 75, who underwent microsurgical treatment of COM from 2015 to 2018. Patients were divided into two groups based on the presence or absence of AC of the middle ear: 97 with cholesteatoma (CCOM) and 81 without cholesteatoma (COM). Samples of the perimatrix of AC and inflamed middle ear mucosa were taken intraoperatively. The condition of the tympanic cavity mucosa was examined by otomicroscopy exploration intraoperatively. The expression levels of TNF-a, IL-1 and MMP-9 were determined by immunohistochemical analysis. Results: The difference in the percentage distribution of patients according to the condition of the tympanic cavity mucosa between both groups was statistically significant (p <0.01) where in the COM group the highest frequency was 43.2% of patients with mucosal hypertrophy, and in the CCOM 56.7% with granulations. With highly positive expression of TNF-R2 and IL-1, a higher probability of the presence of mucosal hypertrophy and granulations can be expected, and with highly positive expression of MMP-9 the presence of granulations. Conclusion: Acquired middle ear cholesteatoma is a statistically significant predictor of the occurence of mucosal hypertrophy and granulations in the tympanic cavity in relation to the control tissue of the inflamed middle ear mucosa. The high expression of TNF-R2, IL-1 and MMP-9 shows a statistically significant association with the presence of granulations and mucosal hypertrophy in acquired middle ear cholesteatoma which may have clinical significance in the evaluation and prognosis of the disease.
Keywords: cholesteatoma; inflammatory mediators; middle ear mucosa